Effect Number of Wire to DC Generator Prototype with Variation Diameter Wire - Rifki Ramadhan; Ferindra Nugrahendi; Tika Erna Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The modern era as now the needs of electricity is enormous. This makes the supply of non-renewable resources dwindling (coal and natural gas). This makes the emergence of smart ideas and innovations by using alternative energy. By using alternative energy we can save the use of non-renewable resources and can create energy efficient environmentally friendly. This study aims to analyze the output power in DC motors by using variations in the number and diameters of the outer coils in order to produce maximum output power value. The research method used is the design and manufacture of tools and experiments by conducting a descriptive research approach. The results of the test using different diameter variations of wire are 0.15 mm, 0.20 mm and 0.25 mm. The voltage test obtained voltage of 0.40 V for wire diameter 0.15 mm, 0.46 V for wire diameter 0.20 mm, and 0.52 V for 0.25 mm wire diameter. Simultaneous current and voltage gain can further improve the efficiency. Keywords: dc generator, magnet, coil